Incidence of Maltreatment of Aboriginal Children Reported to Youth Protection in Quebec: Intercultural Comparisons - Tourigny, Marc; Domond, Pascale; Trocmé, Nico; Sioui, Bruno; Baril, Karine (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2007)
The purpose of the study is to examine reported cases of maltreatment in Aboriginal children and compare them with cases involving non-Aboriginal children based on a sample of such cases reported to Youth Protection services in Quebec. Results indicate that, in Quebec, cases involving Aboriginal children compared with cases for non-Aboriginal children are characterized by living situations such as subsidized housing, substance abuse in parents, an increased number of children in the family, the fact that a case reported was a ‘social emergency’and that a case was less reported by the mother. Intervention plans with Aboriginal families and suggestions for future research are discussed.